Dicephalic Parapagus Tribrachius Conjoined Twins in a Triplet Pregnancy: A Case Report - Kaveh, Mahbod (Tehran University of Medical Sciences, 2014)
Dicephalic parapagus tribrachius conjoined twin is a very rare condition. We present a case of 5-days-old male dicephalic parapagus conjoined twins. The conjoined twins were diagnosed in 4(th) month of pregnancy by ultrasonography. The pregnancy terminates at 36 weeks by cesarean section and triplets were born. The babies were male conjoined twins and another healthy male baby. Many congenital defects of interest can now be detected before birth. Sever form of this malformation precludes postpartum life. It is supposed that with advances in screening methods for prenatal diagnosis these cases are terminated in first or second trimester of pregnancy.